2021
DOI: 10.1016/j.jhin.2020.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Internet of Things management system on hand hygiene compliance in an emergency intensive care unit

Abstract: Background: Hand hygiene is a critical strategy for infection prevention in all healthcare settings. Automated electronic monitoring systems are expected to improve hand hygiene performance. Aim: To investigate the impact of the Internet of Things (IoT) management system on hand hygiene compliance among medical staff in an emergency intensive care unit (EICU). Methods: This retrospective observational study was conducted between July 1 st , 2017 and February 28 th , 2018 in a 19-bed EICU. The changes in hand h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 23 publications
(13 reference statements)
0
10
0
Order By: Relevance
“…We identified 16,791 articles and reviewed 8571 unique titles and abstracts (after removing duplicates across databases) and 440 full-text articles, with 36 studies meeting the predefined eligibility criteria [ 15 , 20 , 22 , 23 , 30 - 61 ]. Study characteristics related to the population, interventions, and outcomes for the 36 included studies are provided in Table S2 in Multimedia Appendix 2 [ 15 , 19 , 21 , 22 , 30 - 60 , 62 ]. The 36 unique articles included 2 (6%) RCTs [ 53 , 54 ] and 34 (94%) quasi-experimental studies [ 15 , 19 , 21 , 22 , 30 - 52 , 55 - 60 , 62 ] (8 non-RCTs and 26 one-group pretest-posttest quasi-experimental designs).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We identified 16,791 articles and reviewed 8571 unique titles and abstracts (after removing duplicates across databases) and 440 full-text articles, with 36 studies meeting the predefined eligibility criteria [ 15 , 20 , 22 , 23 , 30 - 61 ]. Study characteristics related to the population, interventions, and outcomes for the 36 included studies are provided in Table S2 in Multimedia Appendix 2 [ 15 , 19 , 21 , 22 , 30 - 60 , 62 ]. The 36 unique articles included 2 (6%) RCTs [ 53 , 54 ] and 34 (94%) quasi-experimental studies [ 15 , 19 , 21 , 22 , 30 - 52 , 55 - 60 , 62 ] (8 non-RCTs and 26 one-group pretest-posttest quasi-experimental designs).…”
Section: Resultsmentioning
confidence: 99%
“…Study characteristics related to the population, interventions, and outcomes for the 36 included studies are provided in Table S2 in Multimedia Appendix 2 [ 15 , 19 , 21 , 22 , 30 - 60 , 62 ]. The 36 unique articles included 2 (6%) RCTs [ 53 , 54 ] and 34 (94%) quasi-experimental studies [ 15 , 19 , 21 , 22 , 30 - 52 , 55 - 60 , 62 ] (8 non-RCTs and 26 one-group pretest-posttest quasi-experimental designs). Studies were published between 2013 and 2022, apart from 2 studies published in 2008 [ 48 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another retrospective study, Xu et al (2021) measured the effectiveness of an IoT-based management system on HH compliance in an intensive care unit. They found that the new system increased the HH compliance rate among all staff aside from the cleaners [43]. Similarly, in another study, an IoT-based automatic monitoring system was implemented to collect real-time data and employ gamification to improve HH compliance among nurses in both simulation and clinical environments.…”
Section: Internet Of Things and Hand-hygiene Compliancementioning
confidence: 94%
“…Given the recognised importance of hand hygiene in clinical settings, it is not surprising that hospitals were early adopters of technologies that could monitor HH activity [ 18 ]. Despite their lack of sophistication, early Smart devices proved effective in improving hand hygiene compliance [ 19 , 20 , 21 ]. Significant further developments were made possible by the growing acceptance of alcohol-based sanitising gel as an effective alternative to soap and water [ 22 ].…”
Section: Introductionmentioning
confidence: 99%